Characterization of geometrically necessary dislocation evolution during creep of P91 steel using electron backscatter diffraction - Zhang, Kai; Liu, Xinbao; Fan, Ping; Zhu, Lin; Wang, Kai; Wang, Lin; Zhao, Caili (Materials characterization, 2023)
In this study, the change of geometrically necessary dislocation (GND) has been investigated during the elevated temperature creep of P91 steel. Firstly, the crept microstructures of P91 steel at 873 K and 165 MPa were characterized by electron backscatter diffraction (EBSD). Then, the resultant GND distributions were analyzed in detail. Meanwhile, the GND density was quantitatively estimated by two methods of kernel average misorientation (KAM) and Nye's dislocation density tensor, respectively. The obtained results indicated that during creep of P91 steel, the values of GND density calculated by the KAM method are highly consistent with those of Nye's dislocation density tensor method. Besides, the GND density increases significantly during the initial creep stage and attains the maximum approximately at the transition from initial creep to steady creep. During the subsequent creep, it gradually decreases. In addition, it suggested that the internal stress predicted by the obtained GND density is consistent with previous experimental data. Accordingly, it further demonstrated that the present characterization of GND evolution offers a convenient tool for the microstructure degradation analysis of P91 steel during creep. •The microstructure of P91 steel during creep has been investigated by EBSD method.•The change of GND density was quantitatively characterized by KAM and Ney's dislocation density tensor, respectively.•The GND densities obtained by the above methods are highly consistent.•The GND densities vary closely with the creep stage, resulting from the interaction between dislocation and precipitates.